Cytotoxic triosmium carbonyl clusters : are proteins the target? - Lee, Jia Ying (2014)
The interaction of the cytotoxic triosmium carbonyl cluster Os3(CO)10(NCMe)2, 1 with different amino acids and oligopeptides was examined with regard to its selectivity towards the different residues. It was found that 1 was reactive to cysteine, glutamic acid, aspartic acid, glutamine and asparagine, with the propensity for reaction following the order: thiol > carboxylic acid > amide. This was found to be the case for the C, N–protected amino acids, as well as tri– and pentapeptides. Any steric effect from neighboring amino acids appears to be insignificant.